2017
DOI: 10.18632/oncotarget.15057
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary zinc supplementation enhances the epigenetic-activated antioxidant ability of chick embryos from maternal normal and high temperatures

Abstract: The role of maternal dietary zinc supplementation in protecting the embryos from maternal hyperthermia-induced negative effects via epigenetic mechanisms was examined using an avian model (Gallus gallus). Broiler breeder hens were exposed to two maternal temperatures (21°C and 32°C) × three maternal dietary zinc treatments (zinc-unsupplemented control diet, the control diet + 110 mg zinc/kg inorganic or organic zinc) for 8 weeks. Maternal hyperthermia increased the embryonic mortality and induced oxidative dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…The primer sequences are listed in Supplementary Table S1 . The internal references and calculations of relative gene mRNA expression for each target gene were used as described previously [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primer sequences are listed in Supplementary Table S1 . The internal references and calculations of relative gene mRNA expression for each target gene were used as described previously [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MeDIP analysis for the gene promoter was conducted as previously described [ 58 ]. Small fragments of DNA between 600 and 200 bp were prepared by sonication and denatured to produce single-stranded DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao, Yuan, Wang, and Zhan (2016) reported that Se supplementation in the diet of breeders resulted in lower ROS and malondialdehyde (MDA) and higher GSH-Px, SOD and CAT activities in chick embryos exposed to high temperature. Zhu et al (2017) also indicated that maternal dietary zinc could protect chick embryos against maternal heat stress by elevating antioxidant capacity. Present study demonstrated that antioxidant activities of GSH-Px and SOD in chick embryos under high EST were significantly higher in Nano-Se and Nano-ZnO treatments than other heat treatments.…”
Section: In Ovo Injection Of Nano-se and Nano-znomentioning
confidence: 98%
“…However, recent studies in our laboratory have demonstrated that the organic Zn with a moderate chelation strength (Q f value = 30•7) had higher Abbreviations: CON, Zn-unsupplemented basal diet; CuZnSOD, Cu Zn superoxide dismutase; HSP 70 and HSP 90, heat-shock protein 70 and heat-shock protein 90; HT, high temperature; iZn, basal diet supplemented with 110 mg Zn/kg as the inorganic Zn sulphate; MDA, malondialdehyde; MT, metallothionein; NT, normal temperature; oZn, basal diet supplemented with 110 mg Zn/kg as the organic Zn proteinate with a moderate chelation strength (Q f value = 30; 7); ROS, reactive oxygen species. absorption and bioavailability than the inorganic ZnSO 4 , and both liver and pancreas are sensitive tissues to reflect the Zn status of broilers (10)(11)(12)(13)(14)(15) . Nevertheless, it is not clear whether dietary supplementation with Zn, especially the organic Zn with moderate chelation strength, can reduce oxidative damage and increase heat stress resistance with the enhancement of antioxidant ability in broiler breeders.…”
mentioning
confidence: 99%